ANALYSIS OF LEADERSHIP TAXONOMIES AND ORGANIZATIONAL OUTCOMES: EMPIRICAL EVIDENCE FROM MEDIA INDUSTRY OF PAKISTAN - Malik, Kamran Ahmed; Bakhtawar, Barira (European Scientific Journal, ESJ, 2014)
This study was conducted to investigate various leadership taxonomies in media industry of Pakistan and their impact on certain organizational outcomes.The importance of and need for leadership in corporate is ever increasing. Various industries, now a day, are in a constant state of flux, and leaders in its constituting organizations are liable to alter the work settings in order to ensure compatibility with the changes. Furthermore, the recent layers of global recession have also necessitated a reshaping of organizational strategies. In these testing times, the organizations need leaders who can effectively deal with the situation as well as keep their workforce dedicated and motivated. Although there have been numerous international studies on leadership behaviours and organizational outcomes by using Multifactor Leadership Questionnaire, yet such comprehensive studies in the local corporate context have been missing. This was a pure quantitative research aimed at analyzing leadership styles and organizational outcomes through survey research design. For this purpose a questionnaire was designed and data was collected from a sample of 120 respondents. Four hypotheses were developed and tested through regression analysis. Various other statistical techniques including demographical analysis, reliability analysis and correlations were also employed for data analysis. The survey findings show strong correlations between some particular leadership styles and the organizational outcomes. The research significantly highlights the true fit between leadership taxonomies and the organizational outcomes. The research concludes with various ways of devising strategies which can enhance organizational outcomes by adopting appropriate leadership style.